C4d Deposition in Fetal Vessels of the Placenta in Neonatal Lupus Syndrome - Yuichiro Sato; Tomoko Yamaguchi; Jyunsuke Muraoka; Hajime Taniguchi; Atsushi Kisanuki; Kazunari Maekawa; Atushi Yamashita; Murasaki Aman; Yuki Kodama; Hiroshi Sameshima; Yujiro Asada (Case Reports in Obstetrics and Gynecology)
Neonatal lupus syndrome (NLS) is a rare, passively acquired autoimmune syndrome caused by maternal autoantibodies. We describe a case of a newborn with NLS and the accompanying placental findings. A female neonate was born by emergency cesarean delivery due to non-reassuring fetal status at 35 weeks and 3 days. This neonate had congenital erythematous and scar lesions on the face, back, and upper and lower extremities. Maternal and fetal anti-SSA and SSB antibodies were elevated and this baby was diagnosed as NLS. Histologically, the chorionic villi demonstrated capillary shrinkage. An immunohistochemical study revealed complement deposition (C4d) in the capillaries of the villi and umbilical vessels. Our findings suggest that maternal autoantibodies affect the inflammatory response of the fetus through the placenta and that C4d deposition may be useful for diagnosing NLS.